The rates of second lung cancers and the survival of surgically-resected second primary lung cancers in patients undergoing resection of an initial primary lung cancer. (September 2020) - Varlotto, J.M.; Voland, R.; DeCamp, M.M.; Rava, Paul; Fitzgerald, T.J; Maxfield, M.; Lou, F.; Oliveira, P.; Sood, R.; Baima, J.; Zhang, J.; McIntosh, Lacey; et al.
Highlights: Second lung cancer incidence is rising rapidly in females. Second lung cancer incidence in females greatly exceeds all other second cancers. Prolonged lung cancer surveillance after the definitive surgical resection is needed. Surgery for early-stage, second lung cancers yields similar OS and LCSS as primary resection. Abstract: Background: The Lung Cancer Screening Trial demonstrated improved overall survival (OS) and lung cancer specific survival (LCSS), likely due to finding early-stage NSCLC. The purpose of our investigation is to evaluate whether long-term surveillance strategies (4+ years after surgical resection of the initial lung cancer(1LC)) would be beneficial in NSCLC patients by assessing the rates of second lung cancers(2LC) and the OS/LCSS in patients undergoing definitive surgery in 1LC as compared to 2LC (>48 months after 1LC) populations. Methods: SEER13/18 database was reviewed for patients during 1998–2013. Log-rank tests were used to determine the OS/LCSS differences between the 1LC and 2LC in the entire surgical group(EG) and in those having an early-stage resectable tumors (ESR, tumors <4 cm, node negative). Joinpoint analysis was used to determine rates of second cancers 4−10 year after 1LC using SEER-9 during years 1985–2014. Results: The rate of 2LCs was significantly less than all other second cancers until 2001 when the incidence of 2LCs increased sharply and became significantly greater than all other second cancers in females starting in year 2005 and in men starting in year 2010. OS/LCSS, adjusted for propensity score by using inverse probability weighting, demonstrated similar OS, but worse LCSS for 2LCs in the EG, but similar OS/LCSSs in the ESR group. Conclusion: Because the rate of 2LCs are increasing and because the OS/LCSS of the 1LC and 2LC are similar in early-stage lesions, we feel that continued surveillance of patients in order to find early-stage disease may be beneficial.